Equity valuation using multiples:A comparative study showing the best predictor - vaid, mrinal (2011)
This study examines different value driver’s explanatory power on the stock prices. I found this study fascinating as enlightens the reasons behind the extensive use of multiples to estimate equity’s intrinsic value and also consequently influences the existence of multiples during a company’s financial analysis. Two approaches which are used in this paper are the pricing error analysis and Regression analysis for making comparison among the performance of the key value drivers. I also did a comparison between value driver’s performances across different industries. I used data of the all the firms in United States for the period of twenty years i.e. from 1988 to 2007. I got all this data from COMPUSTAT and CRSP. After completing my study I conclude that explains the stock prices reasonably well as they carry value relevant information. Performance results for value drivers across different industries confirmed that industry specific multiples are present.